PENGARUH MINDFULNESS TERHADAP CAREGIVER BURDEN LANSIA DENGAN DEMENSIA DI PANTI WREDA - Heru Ginanjar Triyono; Meidiana Dwidiyanti; Rita Hadi Widyastuti (Jurnal Ilmu Keperawatan Komunitas, 2018)
Data obtained in November 2017 at the time of screening obtained data that there were 35 Caregiver experienced burden with mild to severe category, which consisted of 10 people had a mild burden, 23 moderate burden people and 1 person had a heavy burden. Then at the time of the interview stated that the caregiver felt exhausted because approximately 8 hours of caring for the elderly with dementia, Caregiver also often withstand emotions related to the behavior of elderly people who are difficult to regulate. The research method used in this study was "experimental quasy pre-post test with control group, a sample of 34 people taken by purposive sampling, interventions provided through mindfulness intervention. In the intervention class, there is a significant difference in the caregiver burden level between the pre-test and post-test (p-value = 0,000 <α = 0.05). From these results, the treatment has a significant effect in reducing the Burden Caregiver level. Descriptively, the average level of Burden caregiver in both control classes both pre-test and post-test is at a moderate level. Mindfulness intervention can help caregiver problems that care for the elderly with dementia, emotional caregiver, especially the burden, economic, burden social, psychological burden. Mindfulness is more effective when the active caregiver exercises continuously so that the level of caregiver burden can be reduced